MuTRiG: a mixed signal silicon photomultiplier readout ASIC with high timing resolution and gigabit data link - Chen, Huangshan; Briggl, Konrad; Eckert, Patrick; Harion, Tobias; Munwes, Yonathan; Shen, Wei; Stankova, Vera; Schultz-Coulon, Hans-Christian (Journal of Instrumentation, 2017)
MuTRiG is a mixed signal Silicon Photomultiplier readout ASIC designed in UMC 180 nm CMOS technology for precise timing and high event rate applications in high energy physics experiments and medical imaging. It is dedicated to the readout of the scintillating fiber detector and the scintillating tile detector of the Mu3e experiment. The MuTRiG chip extends the excellent timing performance of the STiCv3 chip with a fast digital readout for high rate applications. The high timing performance of the fully differential SiPM readout channels and 50 ps time binning TDCs are complemented by an upgraded digital readout logic and a 1.28 Gbps LVDS serial data link. The design of the chip and the characterization results of the analog front-end, TDC and the LVDS data link are presented.
Published 17 January 2017
Gesehen am 26.06.2018